Prevention of LPS-Induced Acute Kidney Injury in Mice by Bavachin and Its Potential Mechanisms - Ka-Yun Ban; Ga-Young Nam; Donghee Kim; Yoon Sin Oh; Hee-Sook Jun (MDPI AG, 2022)
Acute kidney injury (AKI) is a serious complication of sepsis with a rapid onset and high mortality rate. Bavachin, an active component of Psoralea corylifolia L., reportedly has antioxidant, anti-apoptotic, and anti-inflammatory effects; however, its beneficial effects on AKI remain undetermined. We investigated the protective effect of bavachin on lipopolysaccharide (LPS)-induced AKI in mice and elucidated the underlying mechanism in human renal tubular epithelial HK-2 cells. Increased serum creatinine and blood urea nitrogen levels were observed in LPS-injected mice; however, bavachin pretreatment significantly inhibited this increase. Bavachin improved the kidney injury score and decreased the expression level of tubular injury markers, such as neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1), in both LPS-injected mice and LPS-treated HK-2 cells. LPS-induced oxidative stress via phosphorylated protein kinase C (PKC) β and upregulation of the NADPH oxidase (NOX) 4 pathway was also significantly decreased by treatment with bavachin. Moreover, bavachin treatment inhibited the phosphorylation of MAPKs (P38, ERK, and JNK) and nuclear factor (NF)-κB, as well as the increase in inflammatory cytokine levels in LPS-injected mice. Krüppel-like factor 5 (KLF5) expression was upregulated in the LPS-treated HK-2 cells and kidneys of LPS-injected mice. However, RNAi-mediated silencing of KLF5 inhibited the phosphorylation of NF-kB, consequently reversing LPS-induced KIM-1 and NGAL expression in HK-2 cells. Therefore, bavachin may ameliorate LPS-induced AKI by inhibiting oxidative stress and inflammation via the downregulation of the PKCβ/MAPK/KLF5 axis.